172k views
18 votes
C = 7a^4+ + 5a²b2 – 3b^4
D=5a^4 + 7a²b^2 + 3b^4
C - D =

2 Answers

11 votes

Answer:

2a^4 +12a


2 {a}^(4) + 12 { a}^(2) \\ * *

User Mabn
by
4.9k points
11 votes

Answer:

C-D is:
\mathbf{4b^4 -2a^b^2 -6b^4}

Explanation:

We are given:


C = 7a^4+ + 5a^2b2 - 3b^4\\D=5a^4 + 7a^2b^2 + 3b^4

We need to find C-D.

Finding C-D we actually have to subtract D from C

So, finding C-D


C-D\\= 7a^4+ + 5a^2b2 - 3b^4-(5a^4 + 7a^2b^2 + 3b^4)\\=7a^4+ + 5a^2b2 - 3b^4-5a^4-7a^2b^2-3b^4

Now, combining the like terms.

Like terms are those that have same variables and exponents.

In our case,
7a^4\: and\: 3b^4, 5a^2b^2\: and\: -7a^b^2, -3b^4\:and\:-3b^4


=7a^4 - 3b^4+5a^2b^2 -7a^b^2 -3b^4-3b^4\\=4b^4 -2a^b^2 -6b^4

So, we get C-D is:
\mathbf{4b^4 -2a^b^2 -6b^4}

User Grandtour
by
5.9k points